Fresnel Zone Antennas - Guo, Y. Jay; Barton, Stephen K. (Springer US, 2002)
This This book book is is a a research research monograph monograph on on Fresnel Fresnel zone zone antennas. antennas. It It covers covers various various lens lens and and reflector reflector antennas antennas based based on on the the Fresnel Fresnel zone zone concept concept and and phase phase correction correction techniques. techniques. The The material material presented presented is is mainly mainly drawn drawn from from the the theoretical theoretical and and experimental experimental work work published published and and unpublished unpublished by by the authors. The book is intended to serve engineers, researchers and the authors. The book is intended to serve engineers, researchers and students in the fields of antennas, microwave and millimetre-wave students in the fields of antennas, microwave and millimetre-wave engineering, engineering, radar, radar, optics optics and and telecommunications. telecommunications. The The authors authors hope hope that that readers readers will will find find the the wealth wealth of of unique unique antenna antenna configurations configurations and and the the theoretical theoretical framework framework presented presented inspirational, inspirational, and and the the large large number number of of equations equations useful useful in in the the analysis analysis and and design design of ofFresnel Fresnel zone zone antennas. antennas. 1. 1 1